The effect of constructing discontinuous side chain D-A structure on high-performance poly (ether sulfone)s optoelectronic materials. (May 2021) - Xing, Zhen; Wang, Yan; Han, Yuntao; Zhai, Yuehui; Tian, Ye; Qi, Shiying; Zhu, Xuanbo; Jiang, Zhenhua; Chen, Zheng
Abstract: The unconjugated high-performance polymers have been developing rapidly in the field of optoelectronics, due to the effective donor-acceptor (D-A) structure design strategy. Poly (ether sulfone) (PES) shows tremendous application potential in the field of optoelectronics by combining with optoelectronic units. Herein, an isolated D-A structure was constructed in the side chain of PES, in which the triphenylamine (TPA) structure was the donor and the imide structure was the acceptor. Electrochemical test showed that the onset potential of PES-TPAs was low (0.55 V). The PES-TPAs as a kind of electrochromic materials could improving their EC cycling stabilities from single-digit cycle times to 52 cycles (20% contrast reduction). To the best knowledge, no detail data was reported on the EC cycling stability of PES-type polymers before this work. Meanwhile, PES-TPAs as a kind of memory storage polymers exhibited a low threshold voltage (−3.03 V). These performances showed a wide application prospect of PES in the field of optoelectronics. More importantly, designing the molecular structure in this way would provide a new select for creating more types of optoelectronic polymers. Graphical abstract: Image 1 Highlights: An isolated D-A structure was constructed in the side chain of PES. They exhibited low onset potential, good EC cycling stability, fast switching time and high optical contrast. They showed low threshold voltage and non-volatile WORM memory characteristic.